Retrievable hydrogel networks with confined microalgae for efficient antibiotic degradation and enhanced stress tolerance - Minwen Jiang; Jie Zheng; Yi Tang; Hai Liu; Yawen Yao; Jianfei Zhou; Wei Lin; Yuan Ma; Jin Liu; Jiajing Zhou (Nature Communications)
Abstract Antibiotic contamination has emerged as a global challenge, increasing antibiotic resistance and threatening human health and ecosystems. Bioremediation using microorganism offers sustainable methods to degrade such pharmaceutical contaminants. However, these microorganisms exhibit reduced activity under high-stress conditions, and are difficult to recycle and potentially leak into environment as microbial pollutions. Here we report bioprinted retrievable microalgae hydrogel networks (MHNs) by confining living microalgae in double-network hydrogels, which achieves enhanced antibiotic degradation (>99.3%) and recyclable ability. Particularly, coating MHN with tannic acid (MHN@TA) generates a semipermeable membrane to prevent the leakage of microalgae (<0.7% for 7 days), ensuring the containment of potential microbial biohazards. The biohybrid system protects the biological activity of microalgae, enabling antibiotic degradation up to 400 mg L−1. Free-standing MHN@TA fencing systems are also manufactured to demonstrate their practical applications. This study provides insights of microalgae-material interactions in bioremediation and offers design rationales for biohybrid systems.